Atividade antifúngica dos fenilpropenos eugenol e isoeugenol sobre cepas de Cryptococcus neoformans - Pinheiro, Lílian Sousa (2017)
Cryptococcus neoformans is an encapsulated yeast of predominantly opportunistic nature, capable of infecting man and animals. Cryptococcosis mainly affects the central nervous system (CNS), with severe and fatal evolution. This mycosis is related to high mortality rates, especially in individuals with compromised immune systems, such as HIV-positive, transplanted and leukemic. Treatment involves a limited number of antifungal agents, with recognized toxicity, resistance and high costs. In this context, the search for antifungal substances in natural products has been a promising alternative with great attention of the students on the use of phenylpropene compounds (eugenol and isoeugenol), due to the wide spectrum of pharmacological properties, including antifungal activity. The aim of the present study was to evaluate the in silico antimicrobial potential of these phenylpropenes and to investigate the in vitro antifungal activity, its possible mechanisms of action and the effect of the association with antifungal against C. neoformans. The analysis of the antimicrobial potential of phenylpropenes was performed in silico using the Pass® online software. The minimum inhibitory concentration (MIC), minimum fungicidal concentration (CFM), the effect of eugenol and isoeugenol on the cell wall (sorbitol assay) and membrane ergosterol binding were performed by the microdilution technique. The effect of the association of products tested with standard antifungal by the checkerboard method was also evaluated. In the in silico study, eugenol and isoeugenol demonstrated a greater propensity to be active, expressed as a percentage, in relation to fungal microorganisms. The tests for antifungal activity revealed that the phenylpropenes studied promoted antifungal effect with IC50 of 16 μg/mL for the C. neoformans strains, as well as fungicidal action due to the presence of CFM50 of 32 μg/mL. In the investigation of the mechanism of antifungal action it was evidenced that the MIC values of eugenol and isoeugenol against C. neoformans remained unchanged in the presence of 0.8 M sorbitol, suggesting that these compounds do not act through the inhibition of fungal cell wall synthesis. On the other hand, phenylpropene MIC values varied (16 to 128 μg / mL) in the presence of ergosterol (400 μg/mL) in the plasma membrane assay, showing that both compounds form complexes with ergosterol. The associations eugenol-amphotericin B and isoeugenol-amphotericin B were antagonists for the strains tested (LM 615 and INCQS 40221). Thus, these phenylpropenes may represent a new possibility among the products with antifungal activity, since they showed promising activity by a mechanism involving the ergosterol complexation present in the membrane of C. neoformans.